2019
DOI: 10.1038/s41598-018-37092-7
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular risk algorithms in primary care: Results from the DETECT study

Abstract: Guidelines for prevention of cardiovascular diseases use risk scores to guide the intensity of treatment. A comparison of these scores in a German population has not been performed. We have evaluated the correlation, discrimination and calibration of ten commonly used risk equations in primary care in 4044 participants of the DETECT (Diabetes and Cardiovascular Risk Evaluation: Targets and Essential Data for Commitment of Treatment) study. The risk equations correlate well with each other. All risk equations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…2) (10,21). Even the mHealth gures for which no laboratory tests were done had a proportional level close to that of ASCVD, which has a high sensitivity for identifying future CVD occurrence of around 80%, with a fairly high speci city (69%) and a positive predictive value (17%) (23). These ndings indicate that at least the mHealth application can be used easily by community members to provide CVD risk predictions.…”
Section: 2mentioning
confidence: 94%
“…2) (10,21). Even the mHealth gures for which no laboratory tests were done had a proportional level close to that of ASCVD, which has a high sensitivity for identifying future CVD occurrence of around 80%, with a fairly high speci city (69%) and a positive predictive value (17%) (23). These ndings indicate that at least the mHealth application can be used easily by community members to provide CVD risk predictions.…”
Section: 2mentioning
confidence: 94%
“…The threshold at which an intervention should be introduced to prevent CVD as proposed by the WHO differs between countries. 4,47,48 Using numerous risk scores, including FRS for CVD, and comparing…”
Section: Outcome Variablesmentioning
confidence: 99%
“…different thresholds (5%, 10%, and 20%), a previous study showed that at the 10% threshold, the FRS has higher sensitivity and specificity. 47 The most recent WHO guidelines include lifestyle change strategies and a 3 to 6 month follow-up for the population with an absolute CVD risk ≥10%. 49…”
mentioning
confidence: 99%
“…Reliable formulas (algorithms) for non-invasive estimation of V02max (maximal oxygen uptake) are available if a stress testing unit is not available. Depending on the severity and the potential risk of the disease [50], a cardiac ultrasound examination is recommended before the commencement of training.…”
Section: Pre-participation Evaluation and Risk Evaluationmentioning
confidence: 99%